PEMANFAATAN EFFECTIVE MICROORGANISM (EM) LIMBAH SAYUR UNTUK PENGOLAHAN LIMBAH LAUNDRY - Rhenny Ratnawati; Annisa Rifka Alifia (Program Studi Teknik Lingkungan, Universitas Pembangunan Nasional Veteran Jawa Timur, 2020)
Laundry waste contains detergent and phosphate which cause environmental pollution, eutrophication and serious health problems in humans. One of the alternative technologies for laundry waste treatment that is environmentally friendly is Effective Microorganisms (EM). Utilization of vegetable waste as EM is carried out because decomposing vegetables have many microorganisms contained. Microorganisms in vegetables are thought to reduce organic waste. This research aimed to assess the efficiency of reducing COD and phosphate levels in laundry wastewater using EM vegetable waste. The number of reactors consisted of 4 reactors where the EM dosage was 0%, 5%, 10% and 15%, respectively. The results showed that the highest efficiency levels of COD with a dose of 0%, 5%, 10% and 15% were 10.2%, 43.9%, 51% and 59.9%. Whereas for the phosphate level the highest reduction efficiency was at a dose of 0%, 5%, 10% and 15% respectively, namely 0.7%, 53.2%, 56.5% and 65.2%. The effective dose to reduce COD and phosphate in laundry waste is 15%.